Reforming Housing and Regional Policies in Korea - Jones, Randall S.. (OECD Economics Department Working Papers, 2008)
The government has introduced five policy packages since August 2005 to stabilise house prices, mainly due to concerns about possible spill-overs from the capital region to other parts of the country, even though the increase on a nation-wide basis has been modest compared to other OECD countries. The planned expansion in housing construction in the capital region will reduce upward pressure on house prices. However, other policies aimed at reducing "speculative" demand and lowering house prices, such as the price ceiling on new houses, are likely to constrain supply and result in stronger price pressures in the longer term. The government should shift its focus from short-term price fluctuations in house prices to creating an efficient housing market, relying more on private-sector supply. Concern about increasing concentration in the capital region should be dealt with through economic instruments to address externalities, such as pollution and congestion, while phasing out the restrictions on construction in the capital region